N005. Adherence to outpatient follow-up visit in inflammatory bowel disease patients - Jaqueline Ribeiro de Barros; Rogério Saad-Hossne; Lígia Yukie Sassaki; Júlio Pinheiro Baima; Mayra de Barros Dorna; Carina de Fátima de Síbia; Fernanda Lofiego Renosto; R Silva; E. Farineli; Robertha Biondi; Maria Grazia Vettorato; Greta Lorenzon; et al. (2016)
Conclusions:The rate of depression in patients with UC in the present study was similar to the results obtained in previous investigations of UC and is approximately twice the rate that is observed in the general population.We identified additional factors that were significantly associated with depression.The results suggest that patients with these factors require increased support to reduce depression.Strategies to improve depression should particularly target and support patients with symptoms of anxiety, as anxiety showed a significant effect on depression in this study.Further investigations are essential to develop reasonable, tailored programs to reduce depressive symptoms.